RECENT ADAVANCE ON MOLECULAR MECHANISMS OF ABIOTIC AND BIOTIC STRESS: MARKER ASSISTED SELECTIONS - Haq, Q.M.I.; Hussain, T.; Alawi, J.K.Al; Siyabi, R.H.Al; Rawahi, S.H.Al (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2022)
Growth in population and climate change possess a challenge to grow crops in the environment of biotic and abiotic stress plants are simultaneously exposed to a combination of biotic and abiotic stresses that limit crop yields or reduced the crop yield under the biotic and biotic stress. Environmental stress conditions such as drought, heat, salinity, cold, or pathogen infection can have a devastating impact on plant growth and yield under field conditions. Both conventional and molecular breeding are used to reduce the stress. The conventional host-plant resistance to various biotic stresses involves quantitative traits at several loci. Markers include physiological and molecular markers for the development of the stress tolerance crop. The advents of molecular genetic technologies have advanced our understanding regarding biotic stress resistance mechanisms. In this review we update the response of plant toward biotic and biotic stress or the function of a specific gene towards improving the performance of a plant against different abiotic and biotic stresses like drought , cold, heat, salt, pests, diseases (fungal, bacterial,) and nematodes have been analysed using transgenic approach. And the method to develop stress tolerance crops through the conventional breeding as well as molecular breeding.